Putting the cunt in cuntemporary dance - Olivia Teresa Due Pyszko 1999- (2024)
This essay will address, analyze and discuss the research behind the concept, method, and process behind the multidisciplinary and site specific club performance clones. It will explain the different theories and ideas that inspired the creation of the piece, collaborating with a musician and visual artists. The performance clones, was my individual project created in my final year of the BA in Contemporary Dance Practices at Iceland University of the Arts. The piece involves a combination of various queer theories and ideas such as radical imagination and the power of cunt, in order to go beyond gender identity/representation, proposing a queer utopia. The theorists, authors and scholars; adrienne maree brown, Audre Lorde and José Muñoz will be made mention of. In this essay I will investigate and discuss their theories, contextualizing them in a critical manner, specifically referring to the queer contemporary dance & club culture in Reykjavik, Iceland - including an interview with the queer visual artist Ójón Ara Svanhildarbur. Finally the journey from theory and conceptualizing, to the usage of methods in the process of creating my individual project, will be elaborated. Their theories were a part of my research behind the concept, method, and process behind the multidisciplinary and site specific club performance clones.